A pilot study of Internet usage patterns in a group of Italian university students (Italian Journal of Public Health, 2012)
Background: despite growing interest in Internet addiction disorder (Iad) among the high school population, very little is known about the potential risks of the use of the Internet for university students. The present survey aimed to collect information on Internet usage patterns in a group of Italian university students.Methods: the sample comprised 600 Italian university students enrolled in various faculties, in two different universities: catania (n=300; 150 males and 150 females) and Palermo (n=300; 150 males and 150 females). The diagnostic Questionnaire for Iad based on 8 criteria was used to categorize the Internet users. In order to better describe students’ Internet usage patterns, 4 other criteria were added. chi-square test (P
Keywords: Internet usage patterns; University students; Internet attitudes and behaviours